Charity run creates awareness on HIV/AIDS - The, Star (The Star (Metro North), 2013)
MORE than 200 people participated in Universiti Utara Malaysia (UUM)'s second HIV/AIDS Run held at its campus in Sintok, Kedah.Organised by the International Association of Students in Economic and Commercial Sciences (Aiesec), the run was aimed at creating awareness and raising funds for patients.